Comparison of Palpability of Lower Limb Pulses with Early Outcome after Acute Ischemic Stroke - Keilani, M.; Lalouschek, W.; Mittlböck, M.; Greisenegger, S.; Crevenna, R. (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2013)
Aim of this study Aim of this explorative study was to compare pulse palpability of lower legs arteries and early outcome within the first week after admission due to acute ischemic stroke (AIS).2 155 patients (m:f=1 166:989; age: median=69; min=18, max=98 years, Body Mass Index: median=26.0, min=14.9, max=61.9 kg/m2) with ischemic stroke and all 8 pulses checked within the first week were included in this cohort study explorative cohort study. Pulse palpability of left and right lower legs arteries was compared with medical complications within 1 week after admission, the National Institute of Health Stroke Scale 24–36 h after admission (NIHSS), and the modified Rankin Scale at 5–7 days after admission (mRS).Significant associations between increased risk for heart failure (p=0.011), urinary infection (p=0.016), ischemic stroke (p=0.030), fever (p=0.049) and bad pulse palpability were observed.The correlation between mRS and bad pulse palpability was marginally significant (rS=0.041, p=0.056). The correlation between NIHSS and bad pulse palpability was slightly higher and correlation was statistically significant (rS=0.095, p<0.0001).In the present study, significant correlations between bad pulse palpability of lower limb arteries and heart failure, urinary infection, ischemic stroke, fever, NIHSS, and marginally with mRS could be shown, respectively. This seems to indicate a poor early outcome of patients with “bad” pulse palpability after AIS. Pulse palpation as a simple, cost-effective, and time sparing examination, is recommended to help to prevent cardiac events in some cases after AIS.
Keywords: ischemic stroke; pulse palpability; early outcome; complications; mobilization